ANALISIS KESALAHAN DALAM MENYELESAIKAN MASALAH SEGIEMPAT DITINJAU DARI PERKEMBANGAN KOGNITIF - Hadiana, Muhammad Rizqi; Widodo, Sri Adi; Setiana, Dafid Slamet (Journal of Honai Math, 2020)
This study aims to describe students' mistakes in solving rectangular problems based on their cognitive development. This research is a descriptive qualitative study with 4 research’s subjects taken based on purposive sampling. Data collection techniques use tests, namely Test of Logical Operations and Problem-solving Tests. Data analysis techniques include reduction, presentation, and data verification. The results of the study show that mistakes that are often made by students are less complete in writing what is known and asked about the problem. At the stage of devising a plan, students are wrong in determining the formula, the complete steps to be used, and do not write an answer. At the stage of carrying out the plan, students tend to immediately calculate what is known in the problem, not even writing answers at all. Students do not check the answer so that the results of their conclusions and conclusions are wrong.